"Who am I to disagree?" A qualitative study of how patients interpret the consent process prior to manual therapy of the cervical spine. (June 2021) - Reed, Meghan B.; Thomson, Oliver P.
Abstract: Background: Clinical practice standards dictate a requirement for osteopaths to gain informed consent prior to any examination or treatment. Despite previous research on adverse events, communication and patient preferences, no published studies were identified that looked qualitatively at patients experiences of informed consent. This study aimed to explore patient perceptions of the consent process in a student-led osteopathy clinic. Methods: Semi-structured interviews were carried out with a purposive sample of seven patients attending a student osteopathy clinic. Interviews were transcribed verbatim, and constructivist grounded theory was used as a framework for data collection, conceptualisation and analysis. Results: One core theme was identified to highlight participants' perception of a hierarchical power-divide. Three further themes were constructed to illustrate perceived key influencers of the consent experience: commitment to symptom resolution; lack of knowledge and; unwilling to cause friction. Conclusions: Patients' experiences of consent were unified through the core theme of situational disempowerment, questioning the efficacy of current informed consent processes. This study has implications for further research into patient and practitioner perceptions and highlights a need for additional training and reflection on existing communication strategies and consent practices.